2014
DOI: 10.1182/blood.v124.21.20.20
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Maintenance after Chemoimmunotherapy Induction in 1st and 2nd Line Improves Progression Free Survival: Planned Interim Analysis of the International Randomized AGMT-CLL8/a Mabtenance Trial

Abstract: Introduction: Chemoimmunotherapy has become a standard approach in previously untreated and also in pretreated CLL. Addition of Rituximab to FC in fit patients has proven superior to chemotherapy alone and more recently aCD20 treatment was shown to improve outcomes in patients treated with Chlorambucil, suggesting that immunotherapy may be of benefit, independent of the chosen chemotherapy backbone. In follicular and mantle cell lymphoma rituximab maintenance treatment has become a clinical standard. While we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…A randomized trial evaluating rituximab maintenance versus observation in patients with CLL after either firstor second-line chemoimmunotherapy also suggested an increase in secondary malignancies in the rituximab maintenance arm compared to the observation arm (6% vs. <1%, respectively), although the rates of t-MDS/AML were not reported. 26 The mechanism by which an increased cumulative dose of rituximab might have caused the apparent increased incidence of t-MDS/AML in the present study is unclear. B-cells have been shown to exert anti-tumor effects through both antibody-mediated cytotoxicity of malignant cells and antigen-presentation to effector T-cells.…”
Section: Discussionmentioning
confidence: 73%
“…A randomized trial evaluating rituximab maintenance versus observation in patients with CLL after either firstor second-line chemoimmunotherapy also suggested an increase in secondary malignancies in the rituximab maintenance arm compared to the observation arm (6% vs. <1%, respectively), although the rates of t-MDS/AML were not reported. 26 The mechanism by which an increased cumulative dose of rituximab might have caused the apparent increased incidence of t-MDS/AML in the present study is unclear. B-cells have been shown to exert anti-tumor effects through both antibody-mediated cytotoxicity of malignant cells and antigen-presentation to effector T-cells.…”
Section: Discussionmentioning
confidence: 73%
“…The recently reported results on PFS with ibrutinib and idelalisib (Byrd et al, 2013Furman et al, 2014) may also indirectly support the concept of long-term continuous treatment of CLL patients to prevent/delay a relapse. Recent interim data suggested that rituximab maintenance prolonged PFS in a randomized phase 3 study (Greil et al, 2014). In addition, results of the interim analysis of a phase 3 randomized study demonstrated that ofatumumab maintenance was well-tolerated and provided significantly prolonged PFS (van Oers et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…New novel antibodies against CD20 challenging rituximab are now being explored [140][141][142] . Rituximab maintenance after chemoimmunotherapy induction in CLL showed feasibility [143] .…”
Section: Rituximabmentioning
confidence: 99%